Short-Wavelength (Violet) Light Protects Mice From Myopia Through Cone Signaling - Strickland, Ryan (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: Exposure to short-wavelength light influences refractive development and inhibits myopic development in many animal models. Retinal mechanisms underlying this response remain unknown. This study used a mouse model of lens-induced myopia to evaluate the effect of different wavelength light on refractive development and dopamine levels in the retina. A possible retinal pathway is tested using a mutant mouse with dysfunctional cones. METHODS: Wild-type C57BL/6J (WT) and ALS/LtJ/Gnat2(cpfl3) (Gnat2(−)(/)(−)) mice were exposed to one of three different light conditions beginning at postnatal day 28: broad-spectrum “white” (420-680 nm), medium wavelength “green” (525 ± 40 nm), and short wavelength “violet” (400 ± 20 nm). One-half of the mice received hyperopic lens defocus. All mice were exposed to the light for 4 weeks; animals were measured weekly for refractive error and axial parameters. Retinal dopamine and the dopamine metabolite 3,4-dihydroxyphenylacetic acid were measured by HPLC. RESULTS: In WT mice, short-wavelength violet light induced hyperopia and violet light inhibited lens-induced myopia when compared with mice exposed to white light. Hyperopia could be attributed to shallower vitreous chambers in WT animals. There were no changes in the levels of dopamine or its metabolite. In Gnat2(−)(/)(−) mice, violet light did not induce hyperopia or inhibit lens-induced myopia. CONCLUSIONS: These findings show that short-wavelength light slows refractive eye growth, producing hyperopic responses in mice and inhibiting lens-induced myopia. The lack of inhibition in mice with dysfunctional cones suggests that cone signaling plays a role in the hyperopic response to short-wavelength (violet) light.